The conservation value of artificial ponds in the Western Cape Province for aquatic beetles and bugs - Apinda-Legnouo, Emelie Arlette (Stellenbosch : Stellenbosch University, 2008)
Thesis (MScConsEcol (Conservation Ecology and Entomology))--University of Stellenbosc, 2007.